Problematika Independensi Bawaslu dalam Sistem Pengawasan Pemilihan Umum di Indonesia - Rena Zulfaidah; M Yahya Wahyudin; Uu Nurul Huda (Lembaga Yasin AlSys, 2026)
Although the independence of election supervisory bodies has been widely examined, research specifically addressing the structural, administrative, and ethical dimensions that weaken the independence of the Election Supervisory Body (Bawaslu) within Indonesia’s electoral supervision system remains limited. This study aimed to analyze the problems affecting Bawaslu’s independence within Indonesia’s electoral supervision system and to formulate a legal reconstruction to strengthen its institutional autonomy. This study employed a normative juridical method using statutory and conceptual approaches. Primary legal materials, secondary literature, and data from decisions of the Election Organization Ethics Council (DKPP) were analyzed qualitatively using descriptive-prescriptive techniques. The results showed that Bawaslu’s independence was constrained by its budgetary dependence on the government, the civil servant status of its secretariat personnel, the politically influenced commissioner recruitment process, limited authority within the Sentra Penegakan Hukum Terpadu framework, and the dualism in resolving electoral process disputes. Data on DKPP sanctions in 2024 also indicated that problems concerning independence stemmed not only from weaknesses in institutional design but also from the weak ethics and personal integrity of election administrators. These findings contribute to the development of the theory of state auxiliary institutions and broaden the understanding of the interrelationship among structural, administrative, and ethical dimensions in the independence of electoral supervision. This study concluded that strengthening Bawaslu’s independence requires comprehensive legal reconstruction through the granting of autonomous investigative authority and the separation of the secretariat’s personnel system from the executive bureaucracy. The implications of this study include a theoretical contribution to the development of electoral law literature and practical recommendations for policymakers in reforming Bawaslu’s institutional structure and ethical oversight mechanisms. Future research should examine more deeply the moral and integrity dimensions of election supervisory officials at various regional levels in Indonesia.